Pengaruh Work Passion, Work Life Balance, dan Stress Kerja terhadap Turnover Intention Studi pada Karyawan PT. BPR Bank Daerah Gunungkidul - Anisya Widyaningrum; Kusuma Chandra Kirana; Epsilandri Septyarini (Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of work passion, work-life balance, and work stress on the turnover intention of employees at PT. BPR Bank Daerah Gunungkidul. Data in the study were collected by distributing questionnaires to all employees of PT. BPR Bank Daerah Gunungkidul, totaling 116 with a five-point Likert scale. The sampling technique used was non-probability sampling with the census method, while the data analysis used included multiple linear regression analysis, t-test, F-test, and test of the coefficient of determination with the help of SPSS version 25.0. The results of the study partially show that the work passion variable does not affect employee turnover intention. Meanwhile, the variable work-life balance and work stress affect employee turnover intention. In addition, the results of this study show that simultaneously work passion, work-life balance, and work stress affect employee turnover intention.